Differences between tree species seedling and adult altitudinal distribution in mountain forests during the recent warm period (1986–2006) (Ecography, 2009)
Spatial fingerprints of climate change on tree species distribution are usually detected at latitudinal or altitudinal extremes (arctic or alpine tree line), where temperatures play a key role in tree species distribution. However, early detection of recent climate change effects on tree species distribution across the overall temperature gradient remains poorly explored. Within French mountain forests, we investigated altitudinal distribution differences between seedling (≤50 cm tall and >1 yr old) and adult (>8 m tall) life stages for 17 European tree taxa, encompassing the entire forest elevation range from lowlands to the subalpine vegetation belt (50–2250 m a.s.l.) and spanning the latitudinal gradient from northern temperate to southern Mediterranean forests. We simultaneously identified seedlings and adults within the same vegetation plots. These twin observations gave us the equivalent of exactly paired plots in space with seedlings reflecting a response to the studied warm period (1986–2006) and adults reflecting a response to a former and cooler period. For 13 out of 17 species, records of the mean altitude of presence at the seedling life stage are higher than that at the adult life stage. The low altitudinal distribution limit of occurrences at the seedling life stage is, on average, 29 m higher than that at the adult life stage which is significant. The high altitudinal distribution limit also shows a similar trend but which is not significant. Complementary analyses using modelling techniques and focusing on the optimum elevation (i.e. the central position inside distribution ranges) have confirmed differences between life stages altitudinal distribution. Seedlings optima are mostly higher than adults optimum, reaching, on average, a 69 m gap. This overall trend showing higher altitudinal distribution at the seedling life stage in comparison to the adult one suggests a main driver of change highly related to elevation, such as climate warming that occurs during the studied period. Other drivers of change that could play an important role across elevation or act at more specific scales are also discussed as potential contributors to explain our results.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd